Classification and possible bacterial infection in outpatients with eczema and dermatitis in China: A cross-sectional and multicenter study. Issue 35 (September 2017) - Wang, Xin; Shi, Xiao-Dong; Li, Lin-Feng; Zhou, Ping; Shen, Yi-Wei
Abstract : Abstract: Little is known about the classification and bacterial infection in outpatients with eczema and dermatitis in China. To investigate the prevalence of eczema and dermatitis in outpatients of dermatology clinics in China, examine classification and proportion of common types of dermatitis and the possible bacterial infection, and analyze the possible related factors. Outpatients with eczema or dermatitis from 39 tertiary hospitals of 15 provinces in mainland China from July 1 to September 30, 2014, were enrolled in this cross-sectional and multicenter study. Among 9393 enrolled outpatients, 636 patients (6.7%) were excluded because of incomplete information. The leading subtypes of dermatitis were unclassified eczema (35.5%), atopic dermatitis (13.4%), irritant dermatitis (9.2%), and widespread eczema (8.7%). Total bacterial infection rate was 52.3%, with widespread eczema, stasis dermatitis, and atopic dermatitis being the leading three (65.7%, 61.8%, and 61.4%, respectively). Clinically very likely bacterial infection has a significant positive correlation with disease duration, history of allergic disease, history of flexion dermatitis, and severe itching. Atopic dermatitis has become a common subtype of dermatitis in China. Secondary bacterial infection is common in all patients with dermatitis, and more attentions should be paid on this issue in other type of dermatitis apart from atopic dermatitis.